Sistem Informasi Audit Penyerapan Anggaran Berbasis Web - Setyo Budi Hartono (Journal of Economic, Bussines and Accounting (COSTING), 2021)
Implementation of Government Regulation No. 60 of 2008 concerning the government's internal control system, which requires an evaluation of the implementation of the budget for each business unit in each government agency. This assessment will be carried out by the Internal Control Department (SPI), which in this case concerns the use of the monthly budget by units and universities at UIN Walisongo Semarang. This audit will advise the consultant on the implementation of the relevant unit budget. An online budget audit program needs to be developed to ensure accurate information. This information system helps SPI auditors determine the performance of absorption of the unit and faculty budget. Audit software development by adopting research and development (R&D). The program developed on the web goes through the planning, system analysis, system model, and system design phases. Tools that include context diagrams and flowcharts are used to illustrate the course of a series of operations in this program. Testing the feasibility of the software using the black box method and the result is an information system that is applied to the budget audit implementation at Walisongo Islamic University in Semarang. Keywords: Information System, Internal Audit Budget Absorption.